MORPHOLOGY OF URBAN SPACE: Model of Configuration using Logic of Space (LoS) Theory in densely populated of Bandung City - Permana, Asep Yudi; Susanti, Indah; Dewi, Nitih Indra Komala; Wijaya, Karto (Universitas Pendidikan Indonesia, 2019)
A city through the years is always growing and developing along with the development of a variety of urban activities. One of the triggers of the development is the city residents. The increase in population resulted in increasingly high demand for settlement. Moreover, the surge in population also occurred in Bandung city, where one of the changes in the use of space is visible in Taman Hewan Balubur-Tamansari. This area is growing and changing from being a compact place to a solid kampong with an extensive use of space. The purpose of this research basically was to reveal the configuration and the visibility of the changes that occurred as well as examine what factors that caused the occurrence of a change in the use of space function in Taman Hewan Balubur-Tamansari in Bandung. Research used a descriptive approach. As for data collection, this study used questionnaire and analysis with LoS (Logic of Space) theory.This study addressed the thought (value system) of the community based on empirical phenomena in the education area of the settlements that are located in the major cities of Indonesia, which was then analyzed in inductive and qualitative ways. Through a qualitative research method using grounded theory, the study was expected to contribute to the vocabulary knowledge of space theory in addressing the urban density of the urban space as the impact of urbanization and student migration. Moreover, research aimed to enrich the theory about the local cultural values settled in the area of education in major cities of Indonesia, where the findings of the local theory eventually provide the realization that the value spaces for people living in the neighborhoods of the city is not only for quantitative aspects, but also for the concept of the basis theory of spaces in the city. All this time, the architectural space theory is always used to the idea of space based on the theory from the West.